Analysis of Spatial-Temporal Changes of Agricultural Land Use During the Last Three Decades in the Araban District of Turkey Using Remote Sensing - Tunc, Erdihan; Tsegai, Awet Tekeste; Çelik, Sevil (Geomatics and Environmental Engineering, 2021)
Agricultural land use and land cover dynamics were investigated in the Araban district of Turkey during the periods 1984‑2019 by the use of Remote Sensing and Geographic Information Systems (GIS). Landsat‑TM and Landsat‑TIRS / OLI satellite imageries were used to determine land use and land cover changes. Using unsupervised classification method of ERDAS 8.3 software, three main agricultural activities were identified namely irrigated farming, dry farming, and horticultural / garden farming. The analysis has revealed that during the last three decades dry farming has decreased significantly by 14.69% (3802.14 ha) whereas horticultural/garden crops and irrigated farming lands have increased by 11.32% (667.19 ha) and 2.51% (2929.41 ha) respectively. Araban has been under intensive agricultural use due to its fertile soil and preference for horticultural crops such as pistachio, grapes and olives that provide more profit over dry farming crops such as wheat and barley has changed land use. Decrease in dry farming in a semi‑arid climate where Araban is located, has a potential ecological consequence, including a rapid drop of groundwater level, drying of wetlands and the disappearance of the biodiversity, thus, a necessary measures should be taken to implement an environmentally friendly, sustainable agriculture and settlement plan.